Hb Fulton-Georgia [α20(B1)His→Pro; HBA1: c.62A>C]: A New α-Globin Variant Coinherited with α-Thalassemia-2 (3.7 kb deletion) and Hb SC Disease. (October 2013) - Zhuang, Lina; Patel, Niren; Bryant, Shanequa; Kutlar, Abdullah; Kutlar, Ferdane; Young, Andrew N.
<x xml:space="preserve">Abstract</x> We report a novel hemoglobin (Hb) variant that we named Hb Fulton-Georgia, caused by a point mutation in exon 1/codon 20 of the α-globin gene [α20(B1)His→Pro; HBA1: c.62A>C]. This α chain variant was identified in an adult African-American female with Hb SC disease who was also heterozygous for the α-thalassemia-2 (α-thal-2) (3.7 kb deletion or αα/–α3.7). The Hb Fulton-Georgia mutation was located on the intact α1-globin gene not involved by α-thal-2. Molecular models indicated that the α20 residue of Hb Fulton-Georgia was the first amino acid of the B helix, and was not involved in α1/β1 or α1/β2 contacts in Hb S [β6(A3)Glu→Val; HBB: c.20A>T] or Hb C [β6(A3)Glu→Lys; HBB: c.19G>A] tetramers. Furthermore, the histidine→proline substitution at α20 did not disrupt the helical structure. High performance liquid chromatography (HPLC) detected Hb Fulton-Georgia in 16.0% of total Hb, consistent with inheritance on the α1 gene. Coinheritance of Hb Fulton-Georgia, heterozygous α-thal-2 and Hb SC disease was associated with a mild phenotype, consisting of microcytosis and anisocytosis, but no anemia or other hematological abnormality.